Generation of 3D random meso-structure of soil-rock mixture and its meso-structural mechanics based on numerical tests - Xu, Wen-jie; Zhang, Hai-yang; Jie, Yu-xin; Yu, Yu-zhen (Journal of Central South University, 2015)
The mesoscopic failure mechanism and the macro-mechanical characteristics of soil-rock mixture (S-RM) under external load are largely controlled by S-RM’s meso-structural features. The objective of this work is to improve the three-dimensional technology for the generation of the random meso-structural models of S-RM, for randomly generating irregular rock blocks in S-RM with different shapes, sizes, and distributions according to the characteristics of the rock blocks’ size distribution. Based on the new improved technology, a software system named as R-SRM 3D for generation and visualization of S-RM is developed. Using R-SRM 3D , a three-dimensional meso-structural model of S-RM is generated and used to study the meso-mechanical behavior through a series of true-triaxial numerical tests. From the numerical tests, the following conclusions are obtained. The meso-stress field of S-RM is influenced by the distribution of the internal rock blocks, and the macro-mechanical characteristics of S-RM are anisotropic in 3D; the intermediate principal stress and the soil-rock interface properties have significant influence on the macro strength of S-RM.